The comparison of numerical simulation of projectile interaction with transparent armour glass for buildings and vehicles. (October 2018) - Binar, Tomáš; Švarc, Jiří; Vyroubal, Petr; Kazda, Tomáš; Rolc, Stanislav; Dvořák, Aleš
Abstract: In the paper, results of a research project based on the numerical simulation of projectile interactions with transparent armour glass for protected objects such as banks, houses of important person or VIP vehicles and of cores in the anti-terrorist systems for the civil population protection (such as barrier around Eiffel Tower) as per STANAG 4569 AEP-55, Volume 1, are presented. The research was concerned with the impact of projectile interaction on the life cycle of transparent armour glass. The study investigated the scope of damage, the delamination of individual layers of transparent armour glass and the depth of projectile penetration at Protection Level 2 [PARTIAL] (7.62 mm × 39 API BZ) and Level 3 (only projectile 7.62 mm × 54R B32 API) at the temperatures of −32 °C, 20 °C and 55 °C. Using the Finite Element Method (FEM), a transparent armour glass simulation model was created for multihit by two projectiles at a predefined distance. For the purpose of calculation, the LS-Dyna explicit solver was employed allowing the evaluation of theoretical numerical models reliability for a specific application of a projectile (pressure wave) impact on an assembly composed of multiple materials. Highlights: The data from the simulation of the projectile shot to transparent armour in an IVECO vehicle correspond with the simulation. Impacts of the used projectile and temperature on the depth of penetration were demonstrated by measurement and simulation. The mechanism of deformation of the individual layers of the armour was described by simulation at different temperatures.